Radio galaxies at TeV energies: Preface - Glawion, Dorit (Galaxies, 2020)
The majority of the known extragalactic sky from TeV gamma-ray energies consists of blazars having plasma jets pointing in the direction of the line-of-sight, which results in a large Doppler boosting of their emission. Up to now, only six galaxies with a larger viewing angle have been detected in the TeV range. These objects also show fascinating properties, such as fast variability or spectral features and are called "radio galaxies". The TeV radio galaxies provide a unique laboratory for studying key aspects of active galactic nuclei. This Special Issue of Galaxies targets these exciting objects.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Active galactic nuclei; Emission: non-thermal; Gamma-rays; Radio galaxies